Study the immunomodulatory effect of hydroxychloroquine in recurrent pregnancy loss patients in their current pregnancy - Singh, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Recurrent pregnancy loss is defined as 3 or more pregnancy loss consecutively. in most of the cases cause of pregnancy loss remains unclear. lethal chromosomal abnormality is commonly found in product of conception. HCQ has an impact on innate immunity by decreasing the circulatory level of interleukin-1, TNF-alpha and interferon-gamma. In this way this creates a normal environment that favour normal pregnancy development. This study was aimed to find out the effect of HCQ in RPL patients who have raised TNF alpha and anti-nuclear antibody. Methods: This is a clinical interventional cross over design study. All patients included in the study were given 200 mg HCQ twice a day with ecosprin 75 mg HS and folic acid 5 mg. After first trimester iron and calcium are also included in the treatment along with previous treatment. HCQ is continued till delivery. Results: The result of this study shows that there is a significant decrease in the serum value of TNF alpha and after treatment with HCQ in three months. The p value is less than 0.001 for TNF alpha and 0.001 for ANA. This shows that HCQ treatment in recurrent miscarriage patients decreases the serum value of TNF and ANA to a significant level and helps in continuation of pregnancy. Conclusion: It can be concluded that the use of HCQ showed a decrease in TNF alpha and antinuclear antibody in an ongoing pregnancy, which diminished the chances of recurrent pregnancy loss.